Integration of the Pirogov interactive anatomy table into anatomy teaching: A comparative study with cadaveric dissection - Nguyen Thien Duc; Nguyen An Ninh; Nguyen Phi Trinh; Le Quang Tuyen; Nguyen Van Hung; Dinh Hoang Khanh; Nguyen Van Luat; Nguyen Huu Phuc Dai; Tran Duc Huy; Chu Duc Hoa; Tran Vuong The Vinh (PLoS ONE, 2026)
Purposes Anatomy is fundamental in medical education, yet cadaveric dissection faces challenges including limited specimens, high costs, and chemical hazards. Interactive anatomy tables such as the Pirogov system offer innovative alternatives, but evidence from Southeast Asia is limited. Methods In a prospective cohort, 188 medical students (139 in Y1 and 49 in Y2) were randomly assigned to the Pirogov table group (Group A, n = 99) or the cadaveric dissection group (Group B, n = 89). Knowledge acquisition was measured using a validated 20-item multiple-choice test before and after the intervention. Student perceptions were evaluated with a 10-item Likert-scale questionnaire covering four domains: knowledge and understanding, spatial visualization and relationships, learning experience and engagement, and effectiveness and practical value. Data were analyzed using paired and independent t-tests and Welch’s t-test. Results Both groups showed significant knowledge gains (Group A: 4.3 ± 1.65 to 5.2 ± 1.75, p < 0.001; Group B: 4.2 ± 1.92 to 5.1 ± 1.64, p < 0.001), with no difference between them (p = 0.656). Likert ratings were consistently high across domains, with means from 4.43 to 4.48. Y1 students reported higher ratings than Y2 in learning experience (p = 0.023). Conclusion The Pirogov table and cadaveric dissection were associated with similar short-term improvements in anatomy knowledge. Students valued the Pirogov table for visualization and engagement. These findings support integrating digital tools with cadaveric dissection to enhance anatomy education, particularly in resource-limited contexts.